Geoelectric potential changes: Possible precursors to earthquakes in Japan - Uyeda, S. (The National Academy of Sciences, 2000)
Whether electromagnetic precursors to earthquakes (EQs) exist is an important question not only for EQ prediction but also for understanding the physical processes of EQ generation. Slow transient geoelectric potential changes have been observed before several recent EQs in Japan. In most cases, they appeared 1–19 days before the EQs, and their duration and intensity were several minutes to 1 h and 1–2 mV/100 m. The changes appeared before five of all six EQs with magnitude ≥ 5 that occurred within 20 km of our stations during the observation period. Changes were also detected at greater epicentral distances (up to 75 km) before two other EQs, including one EQ of magnitude 4.7, which was preceded by a signal simultaneously recorded at three widely separated stations. These geoelectric potential changes have been distinguished through the following criteria from a multitude of other changes, which were noise of various origins. (i) The selected changes were proportional in amplitude to the length of the recording station's short (≈100 m) dipoles and were simultaneously detected also on long (1–10 km) dipoles when the latter were in operation. (ii) No such changes occurred during the observation period that were not followed by EQs. Although the EQ precursory nature of these geoelectric potential changes is admittedly unproven, it seems that the present results warrant continued serious research into the occurrence, generation, and transmission of these signals and their possible causal relationship to EQs.